Phosphorus and Potassium Status in Paddy Soils (Sawah) of Central Lampung Regency - Junita Barus (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2007)
The knowledge about the nutrient status in the lowland soils is one of several ways to maintain soil fertility and increasefarmers income. The objective of this study was to evaluate the status of P20J and K20 content in paddy soils (sawah) at Central lampung regency during the year 2001/2002. Composite soil samples were collected in each different soil types based on mapping technical survey of I : 50.000 scale. Composite soil samples consisting of 5 - 10 sub samples were taken from top layer (0 - 20 em) depth. Soil sampling was taken by using grid system, that is I cm2 in the map represented 25 ha in the field p]OJ and K potential content determined by HCI 25 %. Data were arranged in a descriptive methode and then classified in to three degrees (high, medium and low). High P was> 40 mg P20s/100 g, medium P was 20;.40 mg P201100 g and law P was < 20 mg P;Os/100 g. High K was > 20 mg K20/100 g, medium K was 10 -20 mg K20 /100 g and low K « 10 mg K /IOOg). The results shawed that soil p;OJ status in paddy soils (sawah) of Centra Lampung regency were 61,65 % high, 35,84 % medium and 2,65 % low while K20 status were 6,64% high, 16,02 % medium and 77,34% low.